Peran Filsafat Dalam Transformasi Masyarakat Menurut John Dewey - CB. Mulyatno (Arete, 2018)
Most people and academics think that philosophy is too difficult, abstract and complicated. Philosophy is a discipline that only elites can learn. This implies two things. First, philosophy has not been understood in the wider community. Second, many people do not yet understand well the meaning and role of philosophy for actual life today. In other words, the relevance of philosophy is questionable. John Dewey is a philosopher who explores the meaning and role of philosophy in developing a social life. From a pragmatic and instrumental perspective, he underlines the meaning and role of philosophy in social life. With a qualitative approach, this literature study of John Dewey’s thought finds three important things. First, as an intellectual movement, philosophy is the process of transforming the life of society. It is an integral part with the experience of human life in finding the meaning of life. Secondly, to inforce the role of philosophical reflection in serving the human development, it is necessary to reconstruction of philosophy. Third, continuous philosophizing is a process of education. It is to improve the quality of human thinking and of human moral conduct in society.